PERBANDINGAN METODE PENETAPAN KADAR SIMETIDIN MENGGUNAKAN SPEKTROFOTOMETRI UV DAN KROMATOGRAFI CAIR KINERJA TINGGI - Aqnes Budiarti; Adina Fitria K.W.; Sumantri Sumantri (Universitas Wahid Hasyim Semarang, 2016)
ABSTRACT Determination ofdrug substance is one of the drug quality control to ensure the safetyof drug. Determination of cimetidine could use UV spectrophotometry and HPLC. The aim ofthis study were to validate the methode using two instruments, to compare both of the method and to apply it intablet dosage forms. Determination of cimetidin using UV spectrophotometry was set on wave length 219 nm. Determination using HPLC with coloumn C18 and mobile phase mixture of methanol: water-phosphoric acid (30:70, v/v), flow rateat 1mL/min and UV detector. The method was validated in terms of accuracy, precision, linearity, selectivity and sensivity. The method of determination of cimetidine using both instruments were campared by analysis of variant. Validation method using UV spectrophotometry showed precision of 0.94%, recovery from 97.50 to 100.91%, good linearity, LOD 0.76 µg/mL and LOQ 2.52µg/mL.Validation using HPLC method resulted value of precision 0.30%, recovery from 98.42 to 101.83%, good linearity, LOD and LOQ of 0.46 and 0.56 µg/mL. The average concentration of cimetidine in tablets by spectrophotometry UV was 101.95%, while in HPLC was 99.69%.The methods accomplied to the requirements according The Indonesian Pharmacopoeia Edition IV. Both methods provided the same results and did not significantly different. Keyword : validation method, cimetidine, UV spectrophotometry, HPLC